2021
DOI: 10.2147/copd.s298678
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoids and Eosinophilic Inflammation of Airways in Stable COPD

Abstract: Purpose: Lipid mediators, particularly eicosanoids, are associated with airway inflammation, especially with the eosinophilic influx. This study aimed to measure lipid mediators and cells in induced sputum, that could possibly reflect the inflammatory process in the bronchial tree of COPD subjects. Patients and Methods: Eighty patients diagnosed with COPD and 37 healthy controls participated in the study. Induced sputum samples were ascertained for differential cell count and induced sputum supernatant concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In a study of eicosanoids from the induced sputum of 76 COPD and 37 current-, former-, and passive-smoker controls, concentrations of LTE4, LTD4, PGD2, PGE2, 8-iso-PGE2, 8-iso-PGF2a, 5-oxo-ETE, 12-oxo-ETE, and 11-dehydro-TBX2 were significantly higher in COPD subjects compared to healthy controls, whereas concentrations of tetranor-PGE-M and tetranor-PGD-M were lower [ 30 ]. There were no differences in eicosanoids or eosinophilia between COPD patients treated with inhaled corticosteroids (ICS) compared to those with bronchodilators only [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of eicosanoids from the induced sputum of 76 COPD and 37 current-, former-, and passive-smoker controls, concentrations of LTE4, LTD4, PGD2, PGE2, 8-iso-PGE2, 8-iso-PGF2a, 5-oxo-ETE, 12-oxo-ETE, and 11-dehydro-TBX2 were significantly higher in COPD subjects compared to healthy controls, whereas concentrations of tetranor-PGE-M and tetranor-PGD-M were lower [ 30 ]. There were no differences in eicosanoids or eosinophilia between COPD patients treated with inhaled corticosteroids (ICS) compared to those with bronchodilators only [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study of eicosanoids from the induced sputum of 76 COPD and 37 current-, former-, and passive-smoker controls, concentrations of LTE4, LTD4, PGD2, PGE2, 8-iso-PGE2, 8-iso-PGF2a, 5-oxo-ETE, 12-oxo-ETE, and 11-dehydro-TBX2 were significantly higher in COPD subjects compared to healthy controls, whereas concentrations of tetranor-PGE-M and tetranor-PGD-M were lower [ 30 ]. There were no differences in eicosanoids or eosinophilia between COPD patients treated with inhaled corticosteroids (ICS) compared to those with bronchodilators only [ 30 ]. In a serum study of healthy smokers ( n = 37), COPD smokers ( n = 41), and non-smokers ( n = 37), Chen et al identified 17 metabolites that were differentially expressed in COPD smokers compared to both healthy smokers and healthy non-smokers, but that were not significantly different between healthy smokers and non-smokers [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, these metabolites are found in high concentrations in sputum from patients with chronic obstructive pulmonary disease associated eosinophilic airway inflammation (54). During SARS-CoV-2 infection, cell death generates cell debris and causes a stress response in the endoplasmic reticulum that enhances COX activation (55), but it reduces the activity of 15-hydroxy-PG-dehydrogenase-(NAD 1 ), an enzyme that degrades PGE 2, with a consequent increase in PGE 2 level (8).…”
Section: Discussionmentioning
confidence: 98%
“…The increase of acetate, that is the final product of lipid metabolism, in associated with accelerated lipid catabolism, which is present in COPD patient for their poor nutritional status. The production of ketone bodies, acetoacetate and acetone, may indicate the utilization of storage lipids as an alternative energy resource [ 38 ].…”
Section: Biological Matrices For Metabolomic Studies In Copdmentioning
confidence: 99%